Migration Practices in Europe: Economic and Cultural Factors - Zhibek Syzdykova; Kalybek Koblandin; Nikolay Medvedev (Faculty of Geography, Universitas Gadjah Mada, 2023)
This research aimed to identify the economic and cultural factors of migration in Europe within the context of contemporary economic and social realities. To achieve the research objective, a comprehensive multi-stage research project was developed and implemented, incorporating the advantages of statistical analysis, monitoring, rating and summary statistics. The research relied on harmonized and validated statistical data from 48 European countries, divided into four sub-regions, serving as the informational foundation for the study. Using summary statistics on migration factors in the context of economic and cultural factors made it possible to demonstrate the importance of considering cultural human rights in the country’s migration policy. An interpretation of migration practices in Europe by this means enables us to highlight the cultural context as a determining indicator, based on an analysis of objective indicators in the development of migration processes. Furthermore, the study shows that the high quality of life and cultural attractiveness of the national policy stimulates the migration intentions of a person to seek out countries with more developed economies.The findings of this study hold relevance for policymakers and specialists in public administration, particularly those involved in the regulation and control of migration. Additionally, academic researchers can benefit from the empirical regularities established in this research and the identified prospective avenues for future investigations.